Shake Shack : recipes & stories - Garutti, Randy; Rosati, Mark (Clarkson Potter/Publishers, 2017)
Danny Meyer started Shake Shack with the idea of a hot dog cart in Madison Square Park, and donated 100% of their profits to the park as a "community wealth venture." Now they are Union Square Hospitality Group, offering food in unique environments with warmth and hospitality. Get an insider look at the Shake Shack community around the world-- and learn how to cook Shack-cago Dogs, ShackBurgers, and hand-spun shakes and concretes.